2010
DOI: 10.1016/j.metabol.2009.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat intake promotes the development of hepatic steatosis independently from excess caloric consumption in a murine model

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) results from over-consumption and is a significant and increasing cause of liver failure. The type of diet that is conducive to the development of this disease has not been established and evidence-based treatment options are currently lacking. We hypothesized that the onset of hepatic steatosis is linked to the consumption of a diet with a high fat content, rather than related to excess caloric intake. In addition, we also hypothesized that fully manifested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 44 publications
4
70
2
1
Order By: Relevance
“…These data strongly suggest that in particular the lowering of energy intake, and not so much the lowering of fat intake, is of primary importance to obtain beneficial metabolic effects of a diet intervention. Our results, however, contrast with previous studies showing that when HFD is restricted to the caloric intake of LFD fed mice, insulin resistance and hepatic steatosis are not prevented (de Meijer et al 2010;Petro et al 2004). The lack of more pronounced effects of the LFD may be due to a stronger decrease in energy intake during HFD restriction compared to the LFD (even though fat intake was higher in HFD-CR).…”
Section: Discussioncontrasting
confidence: 99%
“…These data strongly suggest that in particular the lowering of energy intake, and not so much the lowering of fat intake, is of primary importance to obtain beneficial metabolic effects of a diet intervention. Our results, however, contrast with previous studies showing that when HFD is restricted to the caloric intake of LFD fed mice, insulin resistance and hepatic steatosis are not prevented (de Meijer et al 2010;Petro et al 2004). The lack of more pronounced effects of the LFD may be due to a stronger decrease in energy intake during HFD restriction compared to the LFD (even though fat intake was higher in HFD-CR).…”
Section: Discussioncontrasting
confidence: 99%
“…Two previous studies, in fact, reported unfavorable effects in mice that were pair-fed on a HF diet to match the caloric intake of mice on a low-fat diet. A certain iso-caloric treatment was found to result in a decrease in insulin sensitivity in the restricted HF group (Petro et al 2004), whereas a second study reported that HF pair-fed mice develop insulin resistance, hepatic steatosis, and obesity (de Meijer et al 2010). The diets used in both studies, however, contained almost twice as much energy available from fat compared with the diet we used in our study (58 and 60% energy from fat, compared with 30%), which might have evoked a different coping strategy.…”
Section: Discussion Dr Of a Hf Diet Improves Metabolic Health And Promentioning
confidence: 99%
“…Most studies examining the effects of DR, however, have been performed in standard rodent diets that are characterized by a low-fat content (7-9% energy from fat). Only few studies focused on the effect of DR using high-fat diets (HF-DR; Petro et al 2004, Kalupahana et al 2011, de Meijer et al 2010, which is, in fact, more relevant to the current dietary status in most developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse liver expresses GLP2R (El-Jamal et al 2014); however, nothing is known about other species, including humans. Moreover, fatty liver is strongly associated with insulin resistance (Asrih & Jornayvaz 2013), and non-alcoholic hepatic steatosis has been reported in HFD-fed mice (de Meijer et al 2010, Fraulob et al 2010. Indeed, in HFD-fed mice, chronic treatment with GLP2 (3-33) aggravates dyslipidaemia and hepatic lipid accumulation.…”
Section: Mechanistic Insightmentioning
confidence: 99%